Small‐Molecule‐Directed Hepatocyte‐Like Cell Differentiation of Human Pluripotent Stem Cells. (17th August 2016) - Mathapati, Santosh; Siller, Richard; Impellizzeri, Agata A.R.; Lycke, Max; Vegheim, Karianne; Almaas, Runar; Sullivan, Gareth J.
Abstract: Hepatocyte‐like cells (HLCs) generated in vitro from human pluripotent stem cells (hPSCs) provide an invaluable resource for basic research, regenerative medicine, drug screening, toxicology, and modeling of liver disease and development. This unit describes a small‐molecule‐driven protocol for in vitro differentiation of hPSCs into HLCs without the use of growth factors. hPSCs are coaxed through a developmentally relevant route via the primitive streak to definitive endoderm (DE) using the small molecule CHIR99021 (a Wnt agonist), replacing the conventional growth factors Wnt3A and activin A. The small‐molecule‐derived DE is then differentiated to hepatoblast‐like cells in the presence of dimethyl sulfoxide. The resulting hepatoblasts are then differentiated to HLCs with N ‐hexanoic‐Tyr, Ile‐6 aminohexanoic amide (Dihexa, a hepatocyte growth factor agonist) and dexamethasone. The protocol provides an efficient and reproducible procedure for differentiation of hPSCs into HLCs utilizing small molecules. © 2016 by John Wiley & Sons, Inc.